Private Boots on The Ground: Meretas Korelasi Kebangkitan Private Military Companies Dengan Globalisasi Ekonomi - Frieska Haridha; Indra Kusumawardhana; Muhammad Firjatullah (Andalas Journal of International Studies (AJIS), 2019)
This article targets an understanding related to the phenomenon of the rise of the Private Military Company which has strengthened its relations with the State in various conflicts in the world in the era of globalization - especially after the terrorist attacks on the United States in 2001. Using PMC understanding as an actor and the concept of globalization on economy, this paper provides a descriptive analysis of the correlation between the existence of PMC and the process of economic globalization that supports their existence in various conflicts in this world.